TEACHING READING COMPREHENSION IN NARRATIVE TEXT THROUGH SKIMMING AND SCANNING - Megawati Basri; Nurlaila Daim; Jasmal Martora (JURNAL PASIFIK PENDIDIKAN, 2022)
The purpose of the study was to see how successful skimming and scanning techniques are at improving students' reading comprehension. This study employed a pre-test and post-test control group design. The research subjects were first-year students from SMP Unggulan Negeri 1 Pulau Morotai. There were 66 students in all, divided into two groups of equal size: an experimental group and a control group. The results show that students or (33) got deficient levels in the control class. After the students were taught by using the conventional method, there was no improvement. While in the experimental group pre-test results showed that 100 percent of students (33) scored 0-54. After skimming and scanning techniques was applied the students’ score in reading comprehension were higher, this can be seen in the figure, from 100 percent of students (33) 64 percent students who got poor level (0-54), 24 percent students got moderate level, while in the range of scores from 70 to 84, there were 12 students. From these findings, skimming and scanning techniques were clearly beneficial in improving students' reading comprehension.